Adhesive and adhesive composition, adhesive sheet, laminate, and display comprising laminate

The pressure-sensitive adhesive composition, utilizing a high content of 2-octyl(meth)acrylate and specific (meth)acrylate monomers, addresses the challenges of high adhesive strength, corrosion resistance, and high solids differentiation while promoting petroleum resource savings and environmental sustainability.

JP2025037775AActive Publication Date: 2025-03-18TOYO INK MFG CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024015205
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-10-20
Filing Date
2024-02-02
Publication Date
2025-03-18
Estimated Expiration
2044-02-02

AI Technical Summary

Technical Problem

Existing pressure-sensitive adhesives face challenges in achieving high adhesive strength, corrosion resistance, and high solids differentiation while minimizing petroleum resource consumption and environmental impact.

Method used

A pressure-sensitive adhesive composition featuring an acrylic polymer copolymerized from a monomer mixture with a high content of 2-octyl(meth)acrylate, combined with specific (meth)acrylate monomers and optional additives like isocyanate-based curing agents and silane coupling agents, to enhance adhesion, corrosion resistance, and solids content.

Benefits of technology

The solution provides a low viscosity adhesive with high adhesive strength, excellent corrosion resistance, and the ability to achieve high solids differentiation, contributing to petroleum resource savings and environmental sustainability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025037775000001_ABST
    Figure 2025037775000001_ABST
Patent Text Reader

Abstract

To provide an adhesive that can contribute more to petroleum resource saving by increasing the proportion of environmentally friendly materials, wherein the adhesive has low viscosity while exhibiting high adhesion performance to adherends, offers superior corrosion resistance and allows for a higher solid content, as well as an adhesive sheet comprising the adhesive, a laminate, and a display comprising the laminate.SOLUTION: The present invention provides an adhesive comprising an acrylic polymer (A), which is a copolymer of a monomer mixture comprising (a1) 2-octyl (meth)acrylate, (a2) a (meth)acrylic monomer with a homopolymer glass transition temperature of 0°C or more, (a3) other monomers, and a carboxyl group-containing monomer in specific amounts respectively; or an adhesive composition comprising the acrylic polymer (A) and a curing agent (B).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive and a pressure-sensitive adhesive composition, a pressure-sensitive adhesive sheet, a laminate, and a display including the laminate. [Background technology]

[0002] Adhesive sheets having an adhesive layer formed from an adhesive are easy to handle and are therefore used in a wide range of fields, including label applications and medical applications. They are also widely used in various optical displays, such as liquid crystal displays (LCDs) and organic electroluminescence displays (OLEDs). In addition to being used as display devices, optical displays are also used as input devices such as touch panels. A cover panel is installed on the touch panel to protect the surface. Usually, the components constituting these optical displays are bonded together via an adhesive layer. Among these, adhesives used in applications where long-term use is expected, such as marking films, window films, automotive components, and optical displays, require high adhesive strength to the adherend to prevent peeling during use. In applications where an adhesive sheet is bonded to a metallic adherend, corrosion resistance is required because corrosion of the adherend due to the components contained in the adhesive can cause deterioration of the product.

[0003] On the other hand, in order to make it easier to coat when making adhesive sheets, adhesives are generally diluted and adjusted to a low viscosity before use. The solvent used for adjusting the viscosity is required to be as low in content as possible from the viewpoints of cost and handling. In addition, when the solid content of the adjusted solution is low, it tends to be difficult to apply the adhesive thickly and uniformly, so there is a demand for low-viscosity adhesives that can be made to have a higher solid content.

[0004] The adhesives described in Patent Document 1 and Patent Document 2 are adjusted to a solid content of about 35%. When the inventors investigated the adhesives described in Patent Document 1 and Patent Document 2, they found that when the solid content was adjusted to 35% or more, the viscosity became too high, making coating difficult, and it was not possible to increase the solid content. As a result, the high cost of the solvent used and the difficulty of applying a thick layer of adhesive have become major issues.

[0005] Furthermore, Patent Document 3 discloses a pressure-sensitive adhesive composition having low viscosity, but the adhesive strength to an adherend is problematic. In addition to the above-mentioned increasing performance requirements, the depletion of petroleum resources and carbon dioxide emissions from the combustion of petroleum-derived products are becoming issues in the industrial sector in which PSA sheets are used. Therefore, attempts are being made to conserve petroleum resources by using bio-derived materials instead of petroleum-derived materials in various industries, starting with the packaging material field, as well as in the optical and semiconductor fields. One method for increasing the proportion of biologically derived materials in adhesives whose main component is an acrylic polymer is to obtain an acrylic polymer by copolymerizing a monomer mixture containing a (meth)acrylic acid alkyl ester monomer obtained by esterifying a linear alkyl alcohol produced by an organism with (meth)acrylic acid. Furthermore, there are also tackifier resins made from naturally derived ingredients, and by selectively using these, it is possible to achieve environmentally friendly products. Increasing the proportion of environmentally friendly materials can contribute to saving petroleum resources, but the current situation is that only limited environmentally friendly materials are used, and there are issues with the performance that was originally achieved, such as fixation strength and adhesive strength. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2007-264092 A [Patent Document 2] JP 2012-173354 A [Patent Document 3] Special Publication No. 2010-506979 Summary of the Invention [Problem to be solved by the invention]

[0007] The problem that the present invention aims to solve is to provide an adhesive that can contribute to the conservation of petroleum resources by increasing the proportion of environmentally friendly materials, and that has high adhesive performance to adherends, excellent corrosion resistance, and a low viscosity adhesive capable of high solid division, as well as an adhesive sheet and laminate using the same, and a display including the laminate. [Means for solving the problem]

[0008] As a result of extensive investigations, the present inventors have found that the problems of the present invention can be solved in the following aspect, and have thus completed the present invention. That is, the present invention provides a pressure-sensitive adhesive comprising an acrylic polymer (A) which is a copolymer of a monomer mixture, the monomer mixture being 100% by mass, The following monomer (a1) is contained in an amount of 30% by mass or more and less than 99.5% by mass, The monomer (a2) is contained in an amount of 0.1% by mass or more and less than 70% by mass, Furthermore, the following monomer (a3) ​​is contained in an amount of 30 mass% or less, A pressure-sensitive adhesive which may contain less than 0.5% by mass of a monomer having a carboxy group. (a1) 2-Octyl (meth)acrylate (a2) (Meth)acrylate monomers having a homopolymer glass transition temperature of 0°C or higher (excluding monomers having a carboxy group and monomers having a hydroxy group). (a3) A monomer other than the monomer (a1), the monomer (a2), the monomer having a carboxy group, and the monomer having a hydroxy group. Effect of the Invention

[0009] The present invention makes it possible to provide an adhesive that can contribute to the conservation of petroleum resources, has high adhesive strength performance with respect to an adherend, has a low viscosity and is capable of high solidification, and an adhesive sheet and laminate using the same, and a display including the laminate. [Brief description of the drawings]

[0010] [Figure 1] 1 is a schematic cross-sectional view partially showing a laminate of the present invention. [Diagram 2] FIG. 1 is a schematic cross-sectional view partially illustrating a display, which is an example of the use of the laminate of the present invention. [Diagram 3] 1 is a schematic cross-sectional view partially illustrating a pressure-sensitive adhesive sheet of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The pressure-sensitive adhesive composition, pressure-sensitive adhesive sheet, laminate, and display including the laminate according to the present disclosure have the following configurations [1] to

[13] .

[0012] [1] A pressure-sensitive adhesive comprising an acrylic polymer (A) which is a copolymer of a monomer mixture, In 100% by mass of the monomer mixture, The following monomer (a1) is contained in an amount of 30% by mass or more and less than 99.5% by mass, The monomer (a2) is contained in an amount of 0.1% by mass or more and less than 70% by mass, Furthermore, the following monomer (a3) ​​is contained in an amount of 30 mass% or less, A pressure-sensitive adhesive which may contain less than 0.5% by mass of a monomer having a carboxy group. (a1) 2-Octyl (meth)acrylate (a2) (Meth)acrylate monomers having a homopolymer glass transition temperature of 0°C or higher (excluding monomers having a carboxy group and monomers having a hydroxy group). (a3) Other monomers other than the monomer (a1), the monomer (a2), the monomer having a carboxy group, and the monomer having a hydroxy group. [2] The pressure-sensitive adhesive, characterized in that it contains 0.1 mass % or more and less than 50 mass % of monomer (a2) based on 100 mass % of the monomer mixture. [3] The pressure-sensitive adhesive, wherein the monomer (a2) is selected from the group consisting of methyl (meth)acrylate, ethyl methacrylate, isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate and phenyl (meth)acrylate. [4] The pressure-sensitive adhesive described above, wherein the monomer mixture further contains a monomer having a hydroxy group. [5] The pressure-sensitive adhesive characterized in that the monomer mixture contains a total of 0.5% by mass or more and 30% by mass or less of a monomer having a carboxy group and a monomer having a hydroxy group, based on 100% by mass of the monomer mixture. [6] The pressure-sensitive adhesive characterized in that the biomass content is 30% or more. [7] A pressure-sensitive adhesive composition comprising the pressure-sensitive adhesive and a curing agent (B). [8] The pressure-sensitive adhesive composition, wherein the curing agent (B) contains at least one of an isocyanate-based curing agent and an epoxy-based curing agent. [9] The pressure-sensitive adhesive composition, further comprising a silane coupling agent (C).

[10] The pressure-sensitive adhesive composition, wherein the gel fraction is 40% or more.

[11] The pressure-sensitive adhesive composition further comprising less than 50 parts by mass of a tackifier resin (D) per 100 parts by mass of the acrylic polymer (A).

[12] The pressure-sensitive adhesive composition as described above, wherein the tackifier resin (D) has a biomass content of 80% or more.

[13] A pressure-sensitive adhesive layer obtained from the pressure-sensitive adhesive or the pressure-sensitive adhesive composition.

[14] The pressure-sensitive adhesive layer, characterized in that the haze is 1.0 or less.

[15] The pressure-sensitive adhesive layer, characterized in that the dielectric constant at 40 GHz is 5.0 or less.

[16] The pressure-sensitive adhesive layer, characterized in that the dielectric tangent at 40 GHz is 0.1 or less.

[17] The pressure-sensitive adhesive layer, characterized in that the refractive index is 1.45 or more and less than 1.52.

[18] The pressure-sensitive adhesive layer described in

[13] , characterized in that the glass adhesion strength is 10 N / 25 mm or more.

[19] The pressure-sensitive adhesive layer, characterized in that the SUS adhesive strength is 5 N / 25 mm or more.

[20] An adhesive sheet comprising the adhesive layer and a release film.

[21] The pressure-sensitive adhesive sheet, wherein the release film has a thickness of less than 200 μm.

[22] A laminate comprising the pressure-sensitive adhesive layer and a substrate.

[23] The laminate, wherein the thickness of the substrate is less than 500 μm.

[24] The laminate as described above, wherein the substrate is a light-transmitting substrate.

[25] The laminate, characterized in that the total light transmittance is 60% or more.

[26] A display comprising the laminate, a polarizing plate, and an optical element.

[0013] The composition, pressure-sensitive adhesive sheet, laminate and display of the present invention will be described below, but the present invention is not limited thereto. In this specification, the term "(meth)acrylate" includes acrylate and methacrylate, the term "(meth)acryloxy group" includes acryloxy group and methacryloxy group, and the term "monomer" is a monomer having an ethylenically unsaturated group. In addition, in this specification, a numerical range specified by "~" includes the numerical values ​​written before and after "~" as the range of the lower and upper limits. Furthermore, "film" and "sheet" are not distinguished by thickness. In other words, in this specification, a "sheet" includes a thin film-like material, and a "film" includes a thick sheet-like material. Furthermore, the adherend refers to a counterpart to which the pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet is attached. Unless otherwise noted, the various components appearing in this specification may be used independently as a single type or as a combination of two or more types.

[0014] <Adhesive> The pressure-sensitive adhesive of the present invention contains an acrylic polymer (A).

[0015] <Acrylic polymer (A)> The acrylic polymer (A) is a copolymer of a monomer mixture, and contains, in 100% by mass of the monomer mixture, The following monomer (a1) is contained in an amount of 30% by mass or more and less than 99.5% by mass, The monomer (a2) is contained in an amount of 0.1% by mass or more and less than 70% by mass, Furthermore, the following monomer (a3) ​​is contained in an amount of 30 mass% or less, The composition may contain less than 0.5% by mass of a monomer having a carboxy group. (a1) 2-Octyl (meth)acrylate (a2) (Meth)acrylate monomers having a homopolymer glass transition temperature of 0°C or higher (excluding monomers having a carboxy group and monomers having a hydroxy group). (a3) Other monomers other than the monomer (a1), the monomer (a2), the monomer having a carboxy group, and the monomer having a hydroxy group.

[0016] [Monomer (a1)] Monomer (a1) refers to 2-octyl (meth)acrylate and is represented by the following formula (1): Monomer (a1) is a biomass monomer. (Formula 1) JPEG2025037775000002.jpg57163(R1=H, CH3) The content of (a1) is 30% by mass or more and less than 99.5% by mass in 100% by mass of the monomer mixture. If the content of (a1) is less than 30% by mass, the viscosity of the adhesive increases or the adhesive strength decreases, which is not preferable. The lower limit of the content of (a1) is 30% by mass or more to obtain the desired effect, but is preferably 50% by mass or more, and more preferably 70% by mass or more. The higher the content of (a1), the more it contributes to saving petroleum resources, which is preferable.

[0017] [Monomer (a2)] The monomer (a2) is a (meth)acrylate monomer having a homopolymer glass transition temperature of 0° C. or higher. However, even if the (meth)acrylate monomer has a homopolymer glass transition temperature of 0° C. or higher, it does not include those having a carboxy group and a hydroxy group. The glass transition temperature (°C) of homopolymers can be obtained from information from the vendors of various monomers or from the values ​​listed in "Polymer Handbook 3rd Edition" (A WILEY-INTERSCIENCE PUBLICATION, 1989).

[0018] Examples of monomer (a2) include acrylamide, N,N-dimethylacrylamide, methacrylonitrile, acrylonitrile, diacetone acrylamide, methyl (meth)acrylate, ethyl methacrylate, ter-butyl methacrylate, sec-butyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, isopropyl methacrylate, stearyl (meth)acrylate, isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, and phenyl (meth)acrylate. From the viewpoint of improving cohesive strength and adhesive strength, the monomer (a2) is preferably selected from the group consisting of methyl (meth)acrylate, ethyl methacrylate, isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, and phenyl (meth)acrylate. In consideration of the environment, it is more preferable to use isobornyl (meth)acrylate, which is a biomass monomer, as (a2).

[0019] The content of (a2) is 0.1% by mass or more and less than 70% by mass in 100% by mass of the monomer mixture. By including 0.1% by mass or more and less than 70% by mass, cohesive strength and adhesive strength can be ensured. It is more preferably 5% by mass or more and less than 50% by mass, and even more preferably 3% by mass or more and less than 30% by mass.

[0020] [Monomer (a3)] The monomer (a3) ​​is a monomer other than the monomer (a1), the monomer (a2), a monomer having a carboxy group, and a monomer having a hydroxy group, and is not particularly limited. In addition, in consideration of the environment, it is preferable to use a (meth)acrylate which is a biomass monomer as the monomer (a3), and it is more preferable to use a (meth)acrylate having a high biomass ratio.

[0021] (a3) may or may not be contained, but if it is contained, the content is 30% by mass or less in 100% by mass of the monomer mixture. By containing 30% by mass or less, it is possible to suppress an increase in viscosity of the adhesive. In order to suppress an increase in viscosity, the content is preferably 20% by mass or less, more preferably 10% by mass or less.

[0022] The monomer mixture constituting the acrylic polymer (A) preferably further contains at least one of a monomer having a carboxy group and a monomer having a hydroxy group. It may contain both a monomer having a carboxy group and a monomer having a hydroxy group, or only one of them. By containing at least one of a monomer having a carboxy group and a monomer having a hydroxy group, the cohesive strength of the adhesive layer is increased, and it is easy to increase the adhesive strength and heat resistance. In terms of preventing corrosion of the adherend by acid, it is more preferable to contain a monomer having a hydroxy group.

[0023] The total content of the monomer having a carboxy group and the monomer having a hydroxy group is preferably 0.5% by mass to 30% by mass, more preferably 0.5% by mass to 21% by mass, based on 100% by mass of the monomer mixture. By being 0.5% by mass to 30% by mass, curing can be promoted and whitening due to humidity and heat can be prevented. When a monomer having a carboxy group is contained in order to prevent corrosion of an adherend by acid, the content of the monomer having a carboxy group in 100% by mass of the monomer mixture is less than 0.5% by mass.

[0024] The monomer having a carboxy group is not limited as long as it has a carboxy group in the molecule, and specific examples thereof include (meth)acrylic acid, p-carboxybenzyl acrylate, β-carboxyethyl acrylate, maleic acid, monoethyl maleic acid, itaconic acid, citraconic acid, and fumaric acid. Of these, (meth)acrylic acid is preferred from the viewpoint of adhesive strength, and acrylic acid is more preferred.

[0025] The monomer having a hydroxy group is not limited as long as it is a monomer having a hydroxy group in the molecule, and specific examples thereof include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate. Of these, 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate are preferred from the viewpoints of adhesive strength and resistance to moist heat.

[0026] (Production of acrylic polymer (A)) The acrylic polymer (A) can be produced by polymerizing the above-mentioned monomer mixture. The polymerization can be carried out by known polymerization methods such as solution polymerization, bulk polymerization, emulsion polymerization, and suspension polymerization, but solution polymerization is preferred. The solvent used in the solution polymerization is preferably, for example, acetone, methyl acetate, ethyl acetate, toluene, xylene, anisole, methyl ethyl ketone, cyclohexanone, etc. The polymerization temperature is preferably a boiling point reaction at 60 to 120°C. The polymerization time is preferably about 5 to 12 hours.

[0027] The polymerization initiator used in the polymerization is preferably a radical polymerization initiator, and the radical polymerization initiator is generally a peroxide or an azo compound. Examples of the peroxide include dialkyl peroxides such as di-t-butyl peroxide, dicumyl peroxide, t-butylcumyl peroxide, α,α'-bis(t-butylperoxy-m-isopropyl)benzene, and 2,5-di(t-butylperoxy)hexyne-3; Peroxyesters such as t-butyl peroxybenzoate, t-butyl peroxyacetate, and 2,5-dimethyl-2,5-di(benzoylperoxy)hexane; ketone peroxides such as cyclohexanone peroxide, 3,3,5-trimethylcyclohexanone peroxide, and methylcyclohexanone peroxide; Peroxyketals such as 2,2-bis(4,4-di-t-butylperoxycyclohexyl)propane, 1,1-bis(t-butylperoxy)3,3,5-trimethylcyclohexane, 1,1-bis(t-butylperoxy)cyclohexane, and n-butyl-4,4-bis(t-butylperoxy)valerate; Hydroperoxides such as cumene hydroperoxide, diisopropylbenzene hydroperoxide, and 2,5-dimethylcyclohexane-2,5-dihydroperoxide; Diacyl peroxides such as benzoyl peroxide, decanoyl peroxide, lauroyl peroxide, and 2,4-dichlorobenzoyl peroxide; Examples include peroxydicarbonates such as bis(t-butylcyclohexyl) peroxydicarbonate.

[0028] Examples of the azo compound include 2,2'-azobisbutyronitrile such as 2,2'-azobisisobutyronitrile (abbreviation: AIBN) and 2,2'-azobis(2-methylbutyronitrile); 2,2'-azobisvaleronitrile such as 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) and 2,2'-azobis(2,4-dimethylvaleronitrile); 2,2'-azobispropionitriles such as 2,2'-azobis(2-hydroxymethylpropionitrile); Examples include 1,1'-azobis-1-alkanenitriles such as 1,1'-azobis(cyclohexane-1-carbonitrile).

[0029] The polymerization initiator is preferably used in an amount of 0.01 to 10 parts by mass, more preferably 0.1 to 2 parts by mass, based on 100 parts by mass of the monomer mixture.

[0030] (Weight average molecular weight (Mw)) The weight average molecular weight of the acrylic polymer (A) is not particularly limited, but is preferably not more than 2 million, and more preferably not more than 1 million. The weight average molecular weight is a value calculated in terms of polystyrene measured by gel permeation chromatography (GPC).

[0031] <Adhesive composition> The pressure-sensitive adhesive composition of the present invention contains a pressure-sensitive adhesive containing an acrylic polymer (A) and a curing agent (B). If necessary, it may also contain a silane coupling agent (C) and a tackifier resin (D).

[0032] <Hardening agent (B)> The pressure-sensitive adhesive composition of the present invention contains a curing agent (B), and the curing agent (B) can be used without any particular limitation as long as it brings about a crosslinked structure in the pressure-sensitive adhesive composition. The incorporation of the curing agent improves the cohesive strength of the pressure-sensitive adhesive layer, and improves the adhesive strength, heat resistance, and light resistance. The curing agent (B) is preferably one of an isocyanate-based curing agent and an epoxy-based curing agent, since it can appropriately increase the cohesive strength of the adhesive and is less likely to adversely affect other physical properties. As long as it contains at least one of an isocyanate-based curing agent and an epoxy-based curing agent, a known curing agent other than the isocyanate-based curing agent and the epoxy-based curing agent may be used in combination.

[0033] The isocyanate-based curing agent is an isocyanate having two or more isocyanate groups. For example, the isocyanate is preferably an aromatic polyisocyanate, an aliphatic polyisocyanate, an araliphatic polyisocyanate, an alicyclic polyisocyanate, and their biuret, nurate, and adduct, and more preferably an aliphatic polyisocyanate, an alicyclic polyisocyanate, and their biuret, nurate, and adduct from the viewpoint of yellowing resistance.

[0034] Examples of aromatic polyisocyanates include 1,3-phenylene diisocyanate, 4,4'-diphenyl diisocyanate, 1,4-phenylene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 4,4'-toluidine diisocyanate, 2,4,6-triisocyanate toluene, 1,3,5-triisocyanate benzene, dianisidine diisocyanate, 4,4'-diphenyl ether diisocyanate, and 4,4',4"-triphenylmethane triisocyanate.

[0035] Examples of aliphatic polyisocyanates include trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate (also known as HMDI), pentamethylene diisocyanate, 1,2-propylene diisocyanate, 2,3-butylene diisocyanate, 1,3-butylene diisocyanate, dodecamethylene diisocyanate, and 2,4,4-trimethylhexamethylene diisocyanate.

[0036] Examples of the aromatic aliphatic polyisocyanate include ω,ω'-diisocyanate-1,3-dimethylbenzene, ω,ω'-diisocyanate-1,4-dimethylbenzene, ω,ω'-diisocyanate-1,4-diethylbenzene, 1,4-tetramethylxylylene diisocyanate, and 1,3-tetramethylxylylene diisocyanate.

[0037] Examples of alicyclic polyisocyanates include 3-isocyanatemethyl-3,5,5-trimethylcyclohexyl isocyanate (also known as IPDI, isophorone diisocyanate), 1,3-cyclopentane diisocyanate, 1,3-cyclohexane diisocyanate, 1,4-cyclohexane diisocyanate, methyl-2,4-cyclohexane diisocyanate, methyl-2,6-cyclohexane diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), and 1,4-bis(isocyanatemethyl)cyclohexane.

[0038] The biuret form is a self-condensation product having a biuret bond formed by self-condensation of an isocyanate monomer, for example, a biuret form of hexamethylene diisocyanate.

[0039] The nurate form is a trimer of an isocyanate monomer, such as a trimer of hexamethylene diisocyanate, a trimer of isophorone diisocyanate, or a trimer of tolylene diisocyanate.

[0040] The adduct is a bifunctional or higher isocyanate compound obtained by reacting an isocyanate monomer with a bifunctional or higher low-molecular active hydrogen-containing compound. Examples of the adduct include a compound obtained by reacting trimethylolpropane with hexamethylene diisocyanate, a compound obtained by reacting trimethylolpropane with tolylene diisocyanate, a compound obtained by reacting trimethylolpropane with xylylene diisocyanate, a compound obtained by reacting trimethylolpropane with isophorone diisocyanate, and a compound obtained by reacting 1,6-hexanediol with hexamethylene diisocyanate.

[0041] The isocyanate compound is preferably a trifunctional isocyanate compound from the viewpoint of forming a sufficient crosslinked structure. The isocyanate compound is more preferably an adduct or nurate, which is a reaction product between an isocyanate monomer and a trifunctional low molecular weight active hydrogen-containing compound. The isocyanate compound is preferably a trimethylolpropane adduct of hexamethylene diisocyanate, a nurate of hexamethylene diisocyanate, a trimethylolpropane adduct of tolylene diisocyanate, a nurate of tolylene diisocyanate, a trimethylolpropane adduct of isophorone diisocyanate, or a nurate of isophorone diisocyanate, and more preferably a trimethylolpropane adduct of hexamethylene diisocyanate, a trimethylolpropane adduct of tolylene diisocyanate, or a trimethylolpropane adduct of isophorone diisocyanate.

[0042] Examples of epoxy curing agents include glycerin diglycidyl ether, 1,6-hexanediol diglycidyl ether, N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N'-diglycidylaminomethyl)cyclohexane, and N,N,N',N'-tetraglycidylaminophenylmethane.

[0043] The curing agent (B) is preferably contained in an amount of 0.02 to 4 parts by mass, and more preferably 0.04 to 1 part by mass, per 100 parts by mass of the acrylic polymer (A). When the content is 0.02 parts by mass or more, the cohesive strength is further improved, and when the content is 4 parts by mass or less, it is easy to achieve both cohesive strength and flexibility, and therefore it is easy to obtain sufficient adhesive strength, heat resistance, and light resistance.

[0044] <Silane coupling agent (C)> The pressure-sensitive adhesive composition of the present invention preferably contains a silane coupling agent (C). By containing the silane coupling agent (C), the adhesive strength, heat resistance, wet heat whitening resistance, and light resistance can be improved. The silane coupling agent (C) is preferably contained in an amount of 0.05 to 0.2 parts by mass per 100 parts by mass of the acrylic polymer (A). By making it 0.05 to 0.2 parts by mass, it becomes easy to achieve both heat resistance, outgassing resistance, and light resistance.

[0045] Examples of the silane coupling agent (C) include an alkoxysilane compound having a (meth)acryloxy group, an alkoxysilane compound having a vinyl group, an alkoxysilane compound having an amino group, an alkoxysilane compound having a mercapto group, and an alkoxysilane compound having an epoxy group. Specific examples of commercially available products include KBM-403 (3-glycidoxypropyltrimethoxysilane), KBE-403 (3-glycidoxypropyltriethoxysilane), KBM-303 (2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane) (all manufactured by Shin-Etsu Chemical Co., Ltd.), BYK-325N (polyether-modified polymethylalkylsiloxane) (manufactured by BYK Japan KK), and the like.

[0046] <Tackifying resin (D)> The pressure-sensitive adhesive composition of the present invention preferably further contains a tackifier resin (D). As the tackifier resin (D), all existing resins such as aliphatic petroleum resins, aromatic petroleum resins, synthetic hydrocarbon resins, terpene resins, rosin resins (rosin, polymerized rosin, hydrogenated rosin, and their esters with glycerin, pentaerythritol, etc., resin acid dimers, etc.), and acrylic resins can be used. The tackifier resin may be used alone or in combination of two or more.

[0047] Examples of aliphatic petroleum resins include Quinton B170 manufactured by Zeon Corporation; examples of aromatic petroleum resins include Nippon Oil Neopolymer L-90 manufactured by JXTG; examples of aliphatic / aromatic petroleum resins include FTR6100 manufactured by Mitsui Chemicals, Inc.; and examples of rosin derivatives include SylvatacRE85 manufactured by Arizona Chemical Company and Superester A-75 manufactured by Arakawa Chemical Industries, Ltd.

[0048] Examples of synthetic hydrocarbon resins include aliphatic petroleum resins, aromatic petroleum resins, aliphatic / aromatic petroleum resins, hydrogenated petroleum resins, coumarone-indene resins, and phenol resins.

[0049] Examples of terpene resins include α-pinene resins, β-pinene resins, dipentene resins, aromatic modified terpene resins, hydrogenated terpene resins, terpene phenol resins, acid modified terpene resins, styrenated terpene resins, and styrene-aliphatic hydrocarbon copolymer resins.

[0050] Examples of rosin-based resins include rosin ester, polymerized rosin, hydrogenated rosin, disproportionated rosin, maleic acid modified rosin, fumaric acid modified rosin, rosin phenolic resin, and natural rosin.

[0051] The content of the tackifier resin (D) is preferably less than 50 parts by mass, more preferably 40 parts by mass or less, per 100 parts by mass of the acrylic polymer (A) in the pressure-sensitive adhesive composition. By including the tackifier resin (D), the adhesive strength to the adherend can be improved.

[0052] In addition, in consideration of the environment, it is more preferable to use a tackifier resin (D) having a biomass content of 80% or more. In addition, the softening point of the tackifier resin (D) is preferably a higher softening point grade in that it can enhance durability at high temperatures, and is preferably 90°C or higher, more preferably 120°C or higher, and even more preferably 140°C or higher.

[0053] The pressure-sensitive adhesive composition of the present invention may contain various resins, chlorinated polyolefins described below, oils, softeners, dyes, pigments, antioxidants, and UV absorbers as optional components, so long as the problem can be solved.

[0054] Examples of chlorinated polyolefins include chlorinated polypropylene, acid-modified chlorinated polypropylene, acrylic-modified chlorinated polypropylene, chlorinated polyethylene, and chlorinated ethylene-vinyl acetate copolymer. From the viewpoints of good compatibility with acrylic polymers and the like and effective reduction in polarity, chlorinated polypropylene and chlorinated ethylene-vinyl acetate copolymer are preferred. Specific examples of commercially available products include Superchlorine 390S (chlorinated polypropylene, chlorine content 36%) and Superchlorine BX (chlorinated EVA, chlorine content 18%) (both manufactured by Nippon Paper Industries Co., Ltd.).

[0055] The pressure-sensitive adhesive composition of the present invention preferably has a gel fraction of 40% or more. However, depending on the application, it may be used even if the gel fraction is 40% or less. The method for measuring the gel fraction will be described in detail in the Examples.

[0056] The pressure-sensitive adhesive composition of the present invention contains the acrylic polymer (A), which is a copolymer of a monomer mixture containing a specific monomer, and thus has the effect of suppressing the increase in viscosity that occurs when using an acrylic polymer, and can ensure high adhesive strength to an adherend, thereby making it possible to significantly reduce the amount of organic solvent used to adjust the viscosity during application compared to conventional methods. In the present invention, when the weight average molecular weight of the acrylic polymer (A) is 1.9 to 2.0 million, the viscosity at a solid content of 15% (±1) is preferably 3000 mPas·s or less, when it is 700,000 to 900,000, the viscosity at a solid content of 35% (±1) is preferably 3000 mPas·s or less, and when it is 400,000 to 500,000, the viscosity at a solid content of 50% (±1) is preferably 3000 mPas·s or less. The method for preparing the solid content and the method for measuring the viscosity will be described in detail in the Examples.

[0057] <Adhesive layer> The pressure-sensitive adhesive layer is a layer obtained from the pressure-sensitive adhesive or pressure-sensitive adhesive composition of the present invention. The method for forming the pressure-sensitive adhesive layer is not particularly limited, and may be the same as the coating method described below in the description of the pressure-sensitive adhesive sheet.

[0058] The adhesive layer of the present invention preferably has a haze of 1.0 or less. A haze of 1.0 or less provides higher transparency, and the adhesive layer is less noticeable during use and has high transmittance during optical use, allowing it to be used advantageously. In order to provide a haze of 1.0 or less, it is necessary to consider the type and ratio of monomers used in the adhesive so that the glass transition point of the adhesive does not become too high. Some monomers used exhibit crystallinity, and the manifestation of crystallinity increases the haze, so it is necessary to similarly consider the type and blending ratio of monomers used with consideration given to crystallinity. The measurement method will be described in detail in the Examples.

[0059] The adhesive layer of the present invention preferably has a dielectric constant of 5.0 or less at 40 GHz. By having a dielectric constant of 5.0 or less at 40 GHz, the optimal operation of a touch sensor or the like can be improved. In order to make the dielectric constant 5.0 or less, it is necessary to lower the polarity of the adhesive. It is necessary to use a compound that is originally low in polarity, or to increase the number of carbon atoms contained in the compound. The measurement method will be described in detail in the Examples.

[0060] The adhesive layer of the present invention preferably has a dielectric loss tangent of 0.1 or less at 40 GHz. By having a dielectric constant of 0.1 or less at 40 GHz, radiation loss of millimeter waves in high frequency bands such as millimeter waves can be suppressed. In order to make the dielectric loss tangent 0.1 or less, it is necessary to reduce the polarity of the adhesive. It is necessary to use a compound with low polarity to begin with, or to increase the number of carbon atoms contained in the compound. The measurement method will be described in detail in the Examples.

[0061] The pressure-sensitive adhesive layer of the present invention preferably has a refractive index of 1.45 or more and less than 1.52. When the pressure-sensitive adhesive layer has a refractive index of 1.45 or more and less than 1.52, it is useful for reducing the reflection of light at the interface between the pressure-sensitive adhesive layer and the optical component when used for bonding between layers of optical components. In order to keep the refractive index within the above range, it is necessary to consider the balance between high refractive index materials and low refractive index materials. This can be adjusted by the composition of the pressure-sensitive adhesive. For example, it can be adjusted by the type of base polymer, the composition ratio of monomer components, the presence or absence of additives, the type and amount of additives used, etc. The measurement method will be described in detail in the examples.

[0062] The adhesive sheet of the present invention preferably has a higher adhesive strength to glass for the purpose of product fixation, etc. Although it is possible to use a low adhesive strength depending on the product, in order to use it for various purposes, the peel strength is preferably 10N / 25mm or more, and more preferably 20N / 25mm or more. The measurement method will be described in detail in the examples. The adhesive sheet of the present invention preferably has a higher adhesive strength than SUS for the purpose of product fixation, etc. Although it is possible to use a low adhesive strength depending on the product, in order to use it for various purposes, the peel strength is preferably 5N / 25mm or more, and more preferably 10N / 25mm or more. The measurement method will be described in detail in the examples.

[0063] <Adhesive sheet> The pressure-sensitive adhesive sheet comprises a pressure-sensitive adhesive layer made of the pressure-sensitive adhesive or pressure-sensitive adhesive composition of the present invention and a release film.

[0064] The pressure-sensitive adhesive sheet of the present invention may have a release film formed on one or both sides of the pressure-sensitive adhesive layer.

[0065] <Release film> The release film is not particularly limited, but a transparent plastic substrate can be suitably used. Examples of the material of the transparent plastic substrate include polyester such as polyethylene terephthalate (PET), acrylic resin such as polymethyl methacrylate (PMMA), polycarbonate, triacetyl cellulose, polysulfone, polyarylate, polycycloolefin, and other plastic materials. The plastic materials can be used alone or in combination of two or more kinds.

[0066] As the release film, among the above-mentioned transparent plastic substrates, a transparent plastic substrate having excellent heat resistance, i.e., a transparent plastic substrate in which deformation is suppressed or prevented under severe conditions such as high temperature, high temperature and high humidity, etc. As the transparent plastic substrate, a PET film or sheet is particularly suitable.

[0067] The thickness of the release film is preferably less than 200 μm. The thickness should be adjusted depending on the handling of the members to be used, but by being less than 200 μm, the material itself is not too stiff, making it easy to wind up into a roll, and it can be used comfortably when laminating sheets, etc.

[0068] The pressure-sensitive adhesive sheet of the present invention has excellent adhesion, and is suitable for forming optical display members such as display devices such as LCDs and OLEDs and input devices such as touch panels, and for bonding these members together. The optical members are not particularly limited, and include PET films, polarizing plates, retardation plates, elliptical polarizing plates, optical compensation films, brightness improvement films, infrared / electromagnetic wave cut films, front anti-reflection films, surface protection films, films having an ITO (indium tin oxide) layer, films having a zinc oxide (ZnO) layer, films obtained by coating or printing metal nanoparticles, films obtained by coating or printing a dispersion containing carbon nanotubes, films obtained by coating or printing a dispersion containing graphene, films obtained by coating or printing a dispersion containing conductive polymers, metal plates formed of SUS, metal meshes, and further laminates thereof.

[0069] When applying the adhesive or adhesive composition, a suitable liquid medium can be added to adjust the viscosity.Specific examples of the solvent include hydrocarbon solvents such as toluene, xylene, hexane, and heptane; ester solvents such as ethyl acetate and butyl acetate; ketone solvents such as acetone and methyl ethyl ketone; halogenated hydrocarbon solvents such as dichloromethane and chloroform; ether solvents such as diethyl ether, methoxytoluene, and dioxane, and other hydrocarbon solvents.However, water and alcohol should be used with caution because they may cause reaction inhibition between the acrylic polymer (A) and the isocyanate curing agent (B).

[0070] The coating method is not particularly limited, and various coating methods can be used, such as a Mayer bar, applicator, brush, spray, roller, gravure coater, die coater, lip coater, comma coater, knife coater, reverse coater, spin coater, etc. In addition, the drying and curing method is not particularly limited, and examples thereof include hot air drying, infrared rays, reduced pressure methods, and active energy rays, but hot air or steam heating at 60 to 180°C is preferred from the viewpoint of outgassing resistance.

[0071] The thickness of the pressure-sensitive adhesive layer is preferably from 2 to 1000 μm, more preferably from 5 to 500 μm. The pressure-sensitive adhesive layer may be in the form of either a single layer or a laminate of two or more layers.

[0072] <Laminate> The laminate of the present invention includes a substrate and a pressure-sensitive adhesive layer. The pressure-sensitive adhesive layer is formed using the pressure-sensitive adhesive sheet of the present invention. Specifically, for example, the release film is peeled off from the pressure-sensitive adhesive sheet of the present invention, and the pressure-sensitive adhesive layer is attached to the substrate to form the laminate.

[0073] <Base material> The substrate refers to the other party to which the adhesive layer of the adhesive sheet having an adhesive layer is attached, and is not limited to a specific one. Examples include polyolefins including polyethylene and polypropylene, resins such as polycarbonate and phenol, metals such as iron, stainless steel (SUS), aluminum and copper, and other materials such as cement, mortar, glass, nonwoven fabric, woven fabric, paper, rubber, foam sheet, and laminates thereof. The adhesive and adhesive composition of the present invention exhibit excellent adhesive strength to at least one type of adherend. The thickness of the substrate is not particularly limited, and is, for example, preferably less than 500 μm, more preferably from 10 to 200 μm, and even more preferably from 25 to 150 μm.

[0074] <Light transparent base material> The laminate of the present invention may also use a light-transmitting substrate as the substrate. A transparent plastic substrate is used as the light-transmitting substrate. Examples of the material for such a light-transmitting substrate include acrylic resins such as polyethylene terephthalate (PET), polyethylene naphthalate, and polymethyl methacrylate (PMMA), and plastic materials such as polycarbonate (PC), polycycloolefin, polyimide, polyphenylene ether, polysulfone, polyethersulfone, polystyrene, and polypropylene. A PET film or PC is preferred, and PC is more preferred in terms of durability. The plastic materials can be used alone or in combination of two or more kinds. The light-transmitting substrate may be subjected to an appropriate surface treatment, for example, a physical treatment such as a corona discharge treatment or a plasma treatment, or a chemical treatment such as an undercoat treatment.

[0075] For a laminate having a light-transmitting substrate, the pressure-sensitive adhesive sheet preferably has a total light transmittance of 60% or more. The laminate having a light-transmitting substrate has a structure of, for example, a light-transmitting substrate / adhesive layer / polarizing plate. In this case, it is preferable to provide the light-transmitting substrate, the adhesive layer, and the polarizing plate in this order. This makes it possible to obtain a laminate having excellent transparency.

[0076] An example of a schematic cross-sectional view partially showing the laminate of the present invention is shown in Fig. 1. In Fig. 1, 3 is a light-transmitting substrate (cover panel), 1 is a pressure-sensitive adhesive layer, and 4 is a polarizing plate.

[0077] In the laminate shown in FIG. 1, a light-transmitting substrate (cover panel) is attached to a polarizing plate via a pressure-sensitive adhesive layer.

[0078] <Manufacture of Laminate> The laminate can be produced, for example, by peeling off the release film from a pressure-sensitive adhesive sheet having release films on both sides of the pressure-sensitive adhesive layer, and attaching the pressure-sensitive adhesive layer to a substrate such as a light-transmitting flexible substrate or a polarizing plate, etc. Alternatively, the pressure-sensitive adhesive layer can be directly formed on the light-transmitting flexible substrate, and then an adhesive layer provided on a substrate or another pressure-sensitive adhesive sheet can be attached to the pressure-sensitive adhesive layer to form a laminate.

[0079] Display The display comprises the laminate of the present invention, a polarizing plate, and an optical element, and thereby has excellent visibility. The optical element is not particularly limited, and examples thereof include a liquid crystal element and an organic EL element.

[0080] Fig. 2 shows an example of a schematic cross-sectional view partially illustrating a display, which is an example of the use of the pressure-sensitive adhesive sheet of the present invention. In Fig. 2, 3 is a light-transmitting substrate (cover panel), 1 is a pressure-sensitive adhesive layer 1, 4 is a polarizing plate, 5 is a pressure-sensitive adhesive layer 2, 6 is a barrier layer such as silicon nitride, 7 is an organic EL layer, 8 is a support such as polyimide, and 9 is an organic EL cell. Note that the configuration of the display is not limited to that shown in Fig. 2.

[0081] In the display shown in Fig. 2, a light-transmitting substrate (cover panel) is attached to a polarizing plate via the pressure-sensitive adhesive layer (pressure-sensitive adhesive layer 1) of the present invention, and is further attached to an organic EL cell via a pressure-sensitive adhesive layer for polarizing plate (pressure-sensitive adhesive layer 2). Thus, the pressure-sensitive adhesive sheet of the present invention can be used in a form in which a transparent pressure-sensitive adhesive layer formed from the pressure-sensitive adhesive is attached to a light-transmitting substrate (cover panel) and a polarizing plate, and the laminate is further attached to an organic EL cell via a pressure-sensitive adhesive layer for polarizing plate. For example, in FIG. 2, the pressure-sensitive adhesive layer of the present invention can be used as either pressure-sensitive adhesive layer 1 or pressure-sensitive adhesive layer 2. In general, when comparing pressure-sensitive adhesive layer 1 and pressure-sensitive adhesive layer 2, the pressure-sensitive adhesive layer 1 has higher quality requirements, and since the pressure-sensitive adhesive of the present invention has good adhesion and bonding properties to the substrate, it is preferably used for pressure-sensitive adhesive layer 1. In this case, the pressure-sensitive adhesive for forming pressure-sensitive adhesive layer 2 may be the pressure-sensitive adhesive of the present invention or a conventionally known pressure-sensitive adhesive.

[0082] There are no particular limitations on the uses of the displays, but examples include OLED televisions, OLED smartphones, OLED tablets, and OLED smartwatches.

[0083] In view of the recent trend toward environmentally friendly materials, the adhesive and adhesive composition of the present invention can be made partially or entirely from biological materials by using a biomass monomer as a monomer constituting the acrylic polymer (A) or by using a biomass tackifier. The biomass degree is preferably 30% or more. The higher the biomass degree is, more preferably 39% or more, and even more preferably 60% or more, the higher the usefulness as an environmentally friendly material. The method for calculating the biomass degree is described in the Examples. EXAMPLES

[0084] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the examples, unless otherwise specified, "parts" means "parts by mass" and "%" means "% by mass". The blending amounts in the tables are parts by mass, and the amounts other than the solvent are calculated as non-volatile contents. The blanks in the tables indicate that no blending was performed. It is technically common knowledge that the viscosity of the adhesive composition increases or decreases depending on the Mw of the acrylic polymer (A) contained therein, and since the Mw of the acrylic polymer (A) can be appropriately adjusted, it is not realistic to confirm the effect of the present invention in all Mw ranges of the acrylic polymer (A). Therefore, in the examples, the acrylic polymer (A) was produced and evaluated so that the Mw was 400,000 to 500,000, 700,000 to 900,000, or 1.9 million to 2 million. The method for measuring the weight average molecular weight of the acrylic polymer is as follows.

[0085] <Measurement of weight average molecular weight (Mw) and Mw classification evaluation method> Weight average molecular weight (Mw) was measured by gel permeation chromatography (GPC). Shimadzu Corporation's GPC device: LC-GPC system "Prominence" was used. Tosoh Corporation's TSKgel α-M columns were used, two of which were connected in series. N,N-dimethylformamide (DMF) was used as the eluent, and measurements were performed at 40°C. Mw was determined by conversion using polystyrene with a known Mw as the standard substance. The weight average molecular weight (Mw) of the acrylic polymer is measured, and the evaluation results are as follows: if it is between 1.9 million and 2 million, the Mw classification is U; if it is between 700,000 and 900,000, the Mw classification is H; and if it is between 400,000 and 500,000, the Mw classification is L.

[0086] (Production of acrylic polymers) <Example 1: Production of (A-1)> Using a reaction apparatus equipped with a stirrer, a reflux condenser, a nitrogen inlet tube, a thermometer, and a dropping tube, ethyl acetate was added as a polymerization solvent to a reaction vessel, and a monomer mixture of 19.75 parts of 2-octyl acrylate (2-OA) as monomer (a1), 20 parts of methyl acrylate (MA) and 3 parts of isobornyl acrylate (IBXA) as monomer (a2), 7 parts of 2-hydroxyethyl acrylate (HEA) and 0.25 parts of 4-hydroxybutyl acrylate (4HBA) as monomer (a3), and azobisisobutyronitrile as an initiator was added. 0.04 parts were charged into a reaction vessel, and a monomer mixture of 19.75 parts of 2-octyl acrylate (2-OA), 20 parts of methyl acrylate (MA) as monomer (a2), 3 parts of isobornyl acrylate (IBXA), 7 parts of 2-hydroxyethyl acrylate (HEA), and 0.25 parts of 4-hydroxybutyl acrylate (4HBA), ethyl acetate as a polymerization solvent, and 0.02 parts of azobisisobutyronitrile as an initiator were added and mixed, and the solution was dropped from the dropping tube over about 2 hours, and polymerized at about 80 ° C. for 6 hours under a nitrogen atmosphere. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain an acrylic polymer solution. The obtained acrylic polymer was designated (A-1). The results of measuring the weight average molecular weight (Mw) of the obtained acrylic polymer are shown in Table 1.

[0087] <Examples 2 to 7, Comparative Production Examples 1 to 7: Production of (A-2 to A-7, A'-1 to A'-7)> Acrylic polymers (A-2 to A-7, A'-1 to A'-7) were produced in the same manner as in the production of the acrylic polymer (Example 1), except that the compositions and blending amounts (parts by mass) were changed to those shown in Table 1. The Mw classification of the obtained acrylic polymers is shown in Table 1.

[0088] [Table 1] <Examples 21 to 24, and 30 to 35: Production of (A-8 to A-17)> Acrylic polymers (A-8 to A-17) were produced in the same manner as in the production of the acrylic polymer (Example 1), except that the compositions and blending amounts (parts by mass) were changed to those shown in Tables 2 and 3. The Mw classification of the obtained acrylic polymers is shown in Table 2.

[0089] [Table 2]

[0090] [Table 3]

[0091] The abbreviations are as follows. Note that only confirmed biomass content is listed. [Monomer (a1)] 2-OA: 2-octyl acrylate (biomass content 73%) 2-OMA: 2-octyl methacrylate (biomass content 67%) [Monomer (a2)] MA: methyl acrylate (Tg: 8°C) MMA: Methyl methacrylate (Tg: 105℃) IBXA: Isobornyl acrylate (Tg: 97°C, biomass content 76%) BMA: Butyl methacrylate (Tg: 20°C) [Monomers with hydroxyl groups (OH monomers) / monomers with carboxyl groups (COOH monomers)] HEA: Hydroxyethyl acrylate 4HBA: 4-Hydroxy n-butyl acrylate AA: Acrylic acid [Other monomers (a3)] 2EHA: 2-ethylhexyl acrylate (Tg: -70℃) BA: n-butyl acrylate (Tg: -55°C, biomass content 57%) LA: Lauryl acrylate (Tg: -23°C, biomass content 80%)

[0092] <Example 8> 0.2 parts of "D-165N" (a biuret of hexamethylene diisocyanate, manufactured by Mitsui Chemicals Inc.) as a curing agent (B) was mixed with 100 parts of the acrylic polymer (A-1) to obtain a pressure-sensitive adhesive composition. The obtained adhesive composition was coated using a comma coater onto a 38 μm thick release liner (SP-PET-O1-BU: manufactured by Mitsui Chemicals Tocello) as a release sheet so that the thickness after drying would be 25 μm. After drying at 110°C for 3 minutes, a 75 μm thick release liner (SP-PET-O3-B3: manufactured by Mitsui Chemicals Tocello) as a release sheet was bonded to the adhesive layer and aged in this state at 23°C for 7 days to obtain an adhesive sheet.

[0093] <Examples 9 to 17, Examples 19 to 20, Examples 25 to 29, Examples 36 to 45, Comparative Examples 1 to 15> As shown in Table 4, pressure-sensitive adhesive compositions and pressure-sensitive adhesive sheets were obtained in the same manner as in Example 8, except that the types and amounts of the acrylic polymer, curing agent (B), silane coupling agent (C), and tackifier resin (D) were changed.

[0094] <Example 18> An adhesive sheet was obtained in the same manner as in Example 8, except that the acrylic polymer (A-5) obtained in Example 5 was used as the adhesive.

[0095] <Gel fraction measurement> The 38 μm release liner of the obtained adhesive sheet was peeled off, and the adhesive layer was attached to a PET film substrate (Toyobo Co., Ltd., Cosmoshine A-4360, thickness 100 μm), and cut into a size of 30 mm wide x 100 mm long to prepare an adhesive sheet for testing. The release liner on the other side of the adhesive tape was peeled off to prepare a test piece, and the weight was measured. The test piece was immersed in ethyl acetate at 23° C. for 24 hours, then removed from the ethyl acetate and dried at 150° C. for 30 minutes. The weight of the test piece after drying was measured, and the gel fraction was calculated using the following formula (1). In Table 4, "40%<" means that the gel fraction is more than 40%. Gel fraction (weight%) = 100 × (W2 - W0) / (W1 - W0) (1) (W0: weight of substrate (PET film), W1: weight of test piece before immersion, W2: weight of test piece after immersion and drying)

[0096] <Biomass ratio calculation> The biomass degree of the pressure-sensitive adhesive composition was calculated using the following formula (2). (In the case of a system consisting of two monomer components (A, B) and one tackifier component (C)) Biomass degree = {(Aw × Ab) + (Bw × Bb) + (Cw × Cb)} / (Aw + Bw + Cw) (2) Aw: weight of monomer A, Bw: weight of monomer B, Cw: weight of tackifier Ab: Biomass ratio of monomer A (%), Bb: Biomass ratio of monomer B (%), Cb: Biomass ratio of monomer C (%), When the biomass degree was specified as a range, the minimum value was used for the above calculation.

[0097] The materials used in the examples and comparative examples are listed below. <Hardening agent (B)> D-165N: Hexamethylene diisocyanate burette manufactured by Mitsui Chemicals Tetrad X: Mitsubishi Gas Chemical Company, multifunctional epoxy resin Aluminum chelate A: Chelate hardener manufactured by Kawaken Fine Chemicals Co., Ltd.

[0098] <Silane coupling agent (C)> KBE-403: (3-glycidoxypropyltriethoxysilane, manufactured by Shin-Etsu Chemical Co., Ltd.) <Tackifying resin (D)> A-100: (Super Ester A-100, Arakawa Chemical Industries, biomass content 95-100%, softening point 95℃-105℃) YS-T160: (YS Polyster T160, Yasuhara Chemical Co., Ltd., biomass content 70%, softening point 160℃)

[0099] The adhesives and adhesive compositions obtained in Examples 8 to 20, 25 to 29, 36 to 45, and Comparative Examples 1 to 15 were evaluated for low viscosity, and the adhesive strength of the adhesive sheets was measured and their corrosion resistance was evaluated by the following methods. Adhesion was judged to be practical if the adhesion to either glass or SUS adherends was evaluated as "usable" or better, and if the adhesion to one adherend was "good", the evaluation of adhesion to the other adherend was omitted. The diagonal lines in Table 5 indicate that no evaluation was performed. The results are shown in Table 5.

[0100] <Low viscosity> The adhesives and adhesive compositions of Examples 8 to 20, 25 to 29, 36 to 45, and Comparative Examples 1 to 15 were measured for viscosity by the method described below and evaluated for low viscosity. When the weight average molecular weight (Mw) of the acrylic polymer contained was 1.9 million to 2 million (U), the solid content was adjusted to 15% (±1); when the Mw was 700,000 to 900,000 (H), the solid content was adjusted to 35% (±1); when the Mw was 400,000 to 500,000 (L), the solid content was adjusted to 50% (±1), and the viscosity was measured using a Brookfield viscometer (rotor number: M3, rotation speed: 12 rpm). The solid content was adjusted using ethyl acetate. [Evaluation Criteria] A: Viscosity less than 3000 mPas·s: Good B: Viscosity of 3000 mPas·s or more and less than 4000 mPas·s: Usable C: Viscosity of 4000 mPas·s or more: Unusable

[0101] <Glass Adhesion> The 38-μm release liner of the obtained adhesive sheet was peeled off, and the adhesive layer was bonded to a PET film (manufactured by Toyobo Co., Ltd., Cosmo Shine A-4360, thickness 100 μm) serving as a base material, and a test adhesive sheet with a size of 25 mm in width × 100 mm in length was prepared by cutting. The other 75-μm release liner of this test adhesive sheet was peeled off, and in an atmosphere of 23°C - relative humidity 50% (50% RH), the adhesive layer was attached to a glass plate and further crimped with a roll according to JIS Z-0237. After 24 hours had elapsed since crimping, the peel strength (peel angle 180°, peel speed 300 mm / min; unit N / 25 mm width) was measured using a tensile testing machine (Tensilon: manufactured by Orientec Co., Ltd.). [Evaluation Criteria] A: Peel strength of 20 N / 25 mm or more.: Good B: Peel strength of 10 N / 25 mm or more and less than 20 N / 25 mm.: Usable C: Peel strength of less than 10 N / 25 mm.: Unusable

[0102] <SUS Adhesion> Measurement was carried out in the same manner as the above glass adhesion measurement, except that the adherend was changed from a glass plate to a SUS plate. [Evaluation Criteria] A: Peel strength of 10 N / 25 mm or more.: Good B: Peel strength of 5 N / 25 mm or more and less than 10 N / 25 mm.: Usable C: Peel strength of less than 5 N / 25 mm.: Unusable

[0103] <Corrosion Resistance> After laminating the adhesive sheet onto the aluminum foil, it was left for 48 hours under high temperature and high humidity conditions of 60 °C and 90% RH. Then, the adhesive sheet was peeled off from the aluminum foil, the surface of the aluminum foil was visually inspected, and evaluation was made according to the following criteria. A: No discoloration was observed on the surface of the aluminum foil. B: Partial discoloration was observed on the surface of the aluminum foil. C: Discoloration was observed on the surface of the aluminum foil.

[0104]

Table 4

[0105] For the adhesive layers of the examples and comparative examples, Haze, dielectric constant, dielectric loss tangent, refractive index, corrosivity, and total light transmittance were measured by the following methods. The measurement results are shown in Table 5.

[0106] <Measurement of Haze and Total Light Transmittance> One separator was peeled off from the double-sided adhesive sheet, and the double-sided adhesive sheet was laminated onto a slide glass (manufactured by Matsunami Glass Industry Co., Ltd., "White Polishing No. 1", thickness 0.8 - 1.0 mm, total light transmittance 92%, haze 0.2%). Then, the other separator was peeled off to prepare a test piece having a layer structure of double-sided adhesive sheet (adhesive layer) / slide glass. The total light transmittance and haze in the visible light region of the above test piece were measured using a haze meter (device name "HM-150", manufactured by Murakami Color Research Laboratory Co., Ltd.) in an environment of 23 ± 1 °C and 52 ± 1% RH. Three samples were prepared for each specimen, and the average of the measured values of these three samples was taken as the total light transmittance and haze in the visible light region.

[0107] <Measurement of Dielectric Constant and Dielectric Loss Tangent> Samples were prepared by laminating 25 microns of PET to both sides of the adhesive layer obtained in the examples or comparative examples, and the dielectric constant and dielectric loss at a frequency of 40 GHz were measured using the following equipment. Three samples were prepared for each specimen, and the averages of the measurements of the three samples were used as the relative dielectric constant and dielectric loss. After the measurements, the measurements of the PET alone were subtracted from the measurements of the three-layer structure of PET-adhesive layer-PET to obtain the measurements of the adhesive layer itself. Measurement method: Cavity resonator method JIS R1641 IPC-TM650 2.5.5.13 Equipment: AET Corporation, dielectric constant measuring device, cavity resonator TE mode Measurement environment: 23±1℃, 52±1%RH

[0108] <Method of measuring refractive index> The refractive index of the adhesive layer at 23° C. is measured using an Abbe refractometer (manufacturer: ERMA, model: ER-2S). [Evaluation Criteria] A: Refractive index is 1.45 or more and less than 1.52: Usable C: Refractive index less than 1.45 or more than 1.52: Not usable

[0109] [Table 5] [Explanation of symbols]

[0110] The symbols in Figures 1, 2 and 3 are explained below. 1 Adhesive layer 1 2 Release film 3 Base material 4. Polarizing Plate 5 Adhesive layer 2 6 Barrier Layer 7 Organic EL layer 8 Support 9 Organic EL Cell

Claims

1. A pressure-sensitive adhesive comprising an acrylic polymer (A) which is a copolymer of a monomer mixture, In 100% by mass of the monomer mixture, The following monomer (a1) is contained in an amount of 30% by mass or more and less than 99.5% by mass: The monomer (a2) is contained in an amount of 0.1% by mass or more and less than 70% by mass, Furthermore, the following monomer (a3) ​​is contained in an amount of 30% by mass or less, A pressure-sensitive adhesive which may contain less than 0.5% by mass of a monomer having a carboxy group. (a1) 2-octyl (meth)acrylate (a2) (meth)acrylate monomers having a homopolymer glass transition temperature of 0° C. or higher (excluding monomers having a carboxy group and monomers having a hydroxy group). (a3) Monomers other than the monomer (a1), the monomer (a2), the monomer having a carboxy group, and the monomer having a hydroxy group.

2. The pressure-sensitive adhesive according to claim 1, characterized in that the monomer (a2) is contained in an amount of 0.1 mass % or more and less than 50 mass % based on 100 mass % of the monomer mixture.

3. 2. The pressure-sensitive adhesive according to claim 1, wherein the monomer (a2) is selected from the group consisting of methyl (meth)acrylate, ethyl methacrylate, isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate and phenyl (meth)acrylate.

4. The pressure-sensitive adhesive according to claim 1, wherein the monomer mixture further contains a monomer having a hydroxy group.

5. The pressure-sensitive adhesive according to claim 4, characterized in that the monomer mixture contains a monomer having a carboxy group and a monomer having a hydroxy group in a total amount of 0.5% by mass or more and 30% by mass or less based on 100% by mass of the monomer mixture.

6. The pressure-sensitive adhesive according to claim 1, having a biomass ratio of 30% or more.

7. A pressure-sensitive adhesive composition comprising the pressure-sensitive adhesive according to claim 1 and a curing agent (B).

8. The pressure-sensitive adhesive composition according to claim 7, wherein the curing agent (B) comprises at least one of an isocyanate-based curing agent and an epoxy-based curing agent.

9. The pressure-sensitive adhesive composition according to claim 7, further comprising a silane coupling agent (C).

10. The pressure-sensitive adhesive composition according to claim 7, which has a gel fraction of 40% or more.

11. The pressure-sensitive adhesive composition according to claim 7 , further comprising less than 50 parts by mass of a tackifier resin (D) per 100 parts by mass of the acrylic polymer (A).

12. The pressure-sensitive adhesive composition according to claim 11, wherein the tackifier resin (D) has a biomass degree of 80% or more.

13. A pressure-sensitive adhesive layer obtained from the pressure-sensitive adhesive according to any one of claims 1 to 6 or the pressure-sensitive adhesive composition according to any one of claims 7 to 12.

14. The pressure-sensitive adhesive layer according to claim 13, which has a haze of 1.0 or less.

15. The pressure-sensitive adhesive layer according to claim 13, having a dielectric constant of 5.0 or less at 40 GHz.

16. The pressure-sensitive adhesive layer according to claim 13, having a dielectric loss tangent of 0.1 or less at 40 GHz.

17. The pressure-sensitive adhesive layer according to claim 13, having a refractive index of 1.45 or more and less than 1.

52.

18. The pressure-sensitive adhesive layer according to claim 13, characterized in that the adhesive strength to glass is 10 N / 25 mm or more.

19. The pressure-sensitive adhesive layer according to claim 13, characterized in that the SUS adhesive strength is 5 N / 25 mm or more.

20. A pressure-sensitive adhesive sheet comprising the pressure-sensitive adhesive layer according to claim 13 and a release film.

21. 21. The pressure-sensitive adhesive sheet according to claim 20, wherein the release film has a thickness of less than 200 μm.

22. A laminate comprising the pressure-sensitive adhesive layer according to claim 13 and a substrate.

23. 23. The laminate of claim 22, wherein the substrate has a thickness of less than 500 μm.

24. 23. The laminate according to claim 22, wherein the substrate is a light-transmitting substrate.

25. 25. The laminate according to claim 24, wherein the total light transmittance is 60% or more.

26. A display comprising the laminate according to claim 24, a polarizing plate, and an optical element.

Citation Information

Patent Citations

  • high shear pressure sensitive adhesive

    JP2009529090A

  • Flame-retardant tape

    JP2014514389A

  • Optical adhesive composition, optical adhesive sheet, image display device and input-output device

    JP2015040237A

  • Optical adhesive, optical film with binder and image display device

    JP2007264092A

  • 2-Octyl (meth)acrylate adhesive composition

    JP2010506979A